Economic evaluation of task-shifting approaches to the dispensing of anti-retroviral therapy - Foster Nicola; McIntyre Diane (BMC, 2012)
Abstract Background A scarcity of human resources for health has been identified as one of the primary constraints to the scale-up of the provision of Anti-Retroviral Treatment (ART). In South Africa there is a particularly severe lack of pharmacists. The study aims to compare two task-shifting approaches to the dispensing of ART: Indirectly Supervised Pharmacist's Assistants (ISPA) and Nurse-based pharmaceutical care models against the standard of care which involves a pharmacist dispensing ART. Methods A cross-sectional mixed methods study design was used. Patient exit interviews, time and motion studies, expert interviews and staff costs were used to conduct a costing from the societal perspective. Six facilities were sampled in the Western Cape province of South Africa, and 230 patient interviews conducted. Results The ISPA model was found to be the least costly task-shifting pharmaceutical model. However, patients preferred receiving medication from the nurse. This related to a fear of stigma and being identified by virtue of receiving ART at the pharmacy. Conclusions While these models are not mutually exclusive, and a variety of pharmaceutical care models will be necessary for scale up, it is useful to consider the impact of implementing these models on the provider, patient access to treatment and difficulties in implementation.